Alterations in epithelial barrier function and host defense responses in chronic rhinosinusitis - Tieu, David D. (2009)
Chronic rhinosinusitis (CRS) is characterized by a chronic symptomatic inflammation of the nasal and paranasal sinus mucosae and is one of the most frequently reported chronic diseases in the United States, with an estimated prevalence of greater than 10% of the general population. Although the pathogenesis of CRS remains poorly understood, there is evidence for a role of bacteria and fungi, as well as the presence of a robust adaptive immune response in the upper airways and sinuses. Recent studies of CRS, as well as several other diseases in the skin and respiratory epithelium, have uncovered evidence that deficiencies in epithelial immune barrier function might compromise the interaction between the host and external immune stimuli. Recent studies suggest the hypothesis that reduced expression of antimicrobial S100 proteins, particularly psoriasin and calprotectin, might lead to increased susceptibility to bacterial and fungal colonization in patients with CRS. The main emphasis of this review will be to highlight the current literature that suggests that a defect in the expression of a broad set of epithelially derived genes might lead to barrier compromise and subsequently a dysfunctional host immune response to environmental agents in patients with CRS.